Evaluation of Antimicrobial Activity of Two Endemic Scrophulariaceae Members - Dulger, Basaran; Hacioglu, Nurcihan (Asian Journal of Chemistry, 2010)
The methanol extracts obtained from endemic Scrophulariaceae members Verbascum vacillans Murb. and Scrophularia depauperata Boiss. have been investigated for their antimicrobial activity. Antimicrobial activity was determined with Escherichia coli ATCC 11230, Staphylococcus aureus ATCC 6538P, Klebsiella pneumoniae UC 57, Pseudomonas aeruginosa ATCC 27853, Proteus vulgaris ATCC 8427, Bacillus cereus ATCC 7064, Mycobacterium smegmatis CCM 2067, Listeria monocytogenes ATCC 15313, Micrococcus luteus CCM 169, Candida albicans ATCC 10231, Rhodotorula rubra DSM 70403, Cryptococcus neoformans ATCC 32308 and Kluyveromyces fragilis ATCC 8608 by disk diffusion method. While the extract of V. vacillans has strong antimicrobial activity against the Grampositive bacteria and yeast cultures, the other plant has weak activity against the test microorganisms used in this study.